The electrical transmission and distribution network in the sectors of Baqubah city - Ibrahim, Marwan Mazhar; Al-Hiti, Mohammad Yusuf Hajim (Edelweiss Applied Science and Technology, 2025)
Baqubah city is supplied by an integrated electrical grid system, starting with a high voltage of 400 kV, then distributed to a low voltage of 132 kV, and then to 33 kV in Baqubah city and the eastern and western zones, each of which consists of two sectors. These zones are distributed among the city's various land uses (residential, industrial, commercial, and governmental). The city also has a population of 128,064 in the eastern zone and 148,449 in the western zone. This network provides a centralized, scheduled power supply service to these uses, where the Electricity Directorate determines the hours of power outages and supply throughout the day, taking into account some urban uses within the city via an emergency line, such as hospitals and central service departments in the governorate administration. The city's need reached (465.51) MW and the supply reached (232.76) MW, which means that there is an energy deficit of (59)%.Baqubah city is supplied by an integrated electrical grid system, starting with a high voltage of 400 kV, then distributed to a low voltage of 132 kV, and then to 33 kV in Baqubah city and the eastern and western zones, each of which consists of two sectors. These zones are distributed among the city's various land uses (residential, industrial, commercial, and governmental). The city also has a population of 128,064 in the eastern zone and 148,449 in the western zone. This network provides a centralized, scheduled power supply service to these uses, where the Electricity Directorate determines the hours of power outages and supply throughout the day, taking into account some urban uses within the city via an emergency line, such as hospitals and central service departments in the governorate administration. The city's need reached (465.51) MW and the supply reached (232.76) MW, which means that there is an energy deficit of (59) %.